2004
DOI: 10.3748/wjg.v10.i13.1881
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunt for palliative treatment of portal hypertension secondary to portal vein tumor thrombosis

Abstract: AIM:To evaluate the palliative therapeutic effects of transjugular intrahepatic portosystemic shunt (TIPS) in portal vein tumor thrombosis (PVTT) complicated by portal hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 26 publications
(6 reference statements)
4
29
0
Order By: Relevance
“…29 In addition, portal venous thrombosis can lead to complications of portal hypertension such as ascites, variceal hemorrhage, and worsening hepatic function in HCC patients. 30 Tumor burden had also been shown to be an important prognostic indicator, but the cutoff used in previous studies has varied from more than 5 cm diameter of the largest nodule to a tumor involving more than 50% of the liver. 31,32 As expected, patients who were eligible for some form of treatment had better survival than those who were too moribund for any treatment.…”
Section: Discussionmentioning
confidence: 99%
“…29 In addition, portal venous thrombosis can lead to complications of portal hypertension such as ascites, variceal hemorrhage, and worsening hepatic function in HCC patients. 30 Tumor burden had also been shown to be an important prognostic indicator, but the cutoff used in previous studies has varied from more than 5 cm diameter of the largest nodule to a tumor involving more than 50% of the liver. 31,32 As expected, patients who were eligible for some form of treatment had better survival than those who were too moribund for any treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TACE will inevitably embolize some part of the blood supplies of normal liver tissues and increase the risk of liver failure. On the other hand, the portal vein pressure is rising with development of PVTT, which increases the risk of esophageal and gastric bleeding and indirectly leads to death [11]. Therefore, opening the occlusion of the portal vein caused by PVTT and reperfusing the portal vein could improve the success of TACE, and this could be achieved using portal vein stenting (PVS) [1214].…”
Section: Introductionmentioning
confidence: 99%
“…Thrombotic occlusion of the portal vein increases the difficulty of the procedure and has prompted several variations in technique to improve technical success [7, 911]. However, when the thrombosis is chronic and associated with cavernous transformation, the success of TIPS has remained limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the thrombosis is chronic and associated with cavernous transformation, the success of TIPS has remained limited. In such patients, Jiang et al reported a 20% (1/5) success rate, with less symptomatic improvement and shorter survival time than noncavernous patients [7]. Walser et al failed in both patients they attempted (0/2) [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation